Pengaruh Sustainability Reporting terhadap Kinerja Keuangan Perusahaan - Yannifar, Afid Firdaus; Idawati, Wiwi (Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
The purpose of this study is to investigate the relationship between sustainability reporting and financial performance. This study uses a panel data set from 189 manufacturing companies listed in 2018-2022. The direct effect is tested using multiple regression techniques. The study finds that sustainability reporting has a negative impact on financial performance, as proxied by return on assets. These results indicate that meeting sustainability reporting indicators will increase costs, which means taking a portion of the profits that could be enjoyed by shareholders.